PENGARUH PEMBERIAN GEL EKSTRAK DAUN PISANG (Musa paradisiaca) TERHADAP WAKTU PENYEMBUHAN LUKA BAKAR DERAJAT II PADA MENCIT - Jayanti, Citra (Coping: Community of Publishing in Nursing; Vol 3 No 1 (2015): JURNAL EDISI JANUARI-APRIL 2015, 2015)
Burn is a skin trauma that caused by heat transfer from heat source to body. Normal Saline is commonly used for burn treatment but this material takes longer time for burn healing. One of the alternative treatments for burn is by using banana leaf extract. Banana leaf consist of some compounds which is needed for burn healing process like flavonoid, tannin, and alkaloid. The aim of this research was to identify effect of banana leaf extract gel for grade two burn healing time among mice. This research was conducted for five weeks in Animal Unit Laboratory Pharmacology Division of Medical Faculty Udayana University and used True experimental post test random sampling with control group design and consist of two groups. Control group was applied with Normal Saline and intervention group applied with banana leaf gel. Based on statistic test Mann-Whitney, the result revealed significant difference between time healing using Normal Saline compared using banana leaf extract with sig. (2-tailed) 0,000 (p value < 0,05) wich means null hypothesis (Ho) was rejected, there was a significant impact of applied banana leaf extract gel for grade two burn healing time among mice.
Keywords: Banana leaf extract gel, time healing, two-grade burn